2008
DOI: 10.1017/s0952523808080048
|View full text |Cite
|
Sign up to set email alerts
|

A reciprocal connection between the ventral lateral geniculate nucleus and the pretectal nuclear complex and the superior colliculus: Anin vitrocharacterization in the rat

Abstract: The ventral lateral geniculate nucleus (vLGN), the pretectal nuclear complex (PNC) and the superior colliculus (SC) are structures that all receive retinal input. All three structures are important relay stations of the subcortical visual system. They are strongly connected with each other and involved in circadian and/or visuomotor processes. However, the information transferred along these pathways is unknown and their possible functions are, therefore, not well understood. Here, we characterized multiple pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…NADPH-d-positive/GABA-IR neurons in the rat DLGN represent a subpopulation of inhibitory interneurons with the ability to affect intrinsic DLGN operations and thalamocortical interactions using neuromodulator NO. Born and Schmidt (2008) reported that inhibitory postsynaptic currents evoked from the pretectal nuclear complex in VLGN neurons are mediated only by GABAA receptors, whereas those evoked in pretectal nuclear complex neurons by VLGN stimulation are mediated either by both GABAA and GABAC receptors or by a GABA receptor with mixed GABAA and GABAC receptor-like pharmacology. Also, they used retrograde double-labeling experiments with two different fluorescent dextran amines to show that pretectal neurons that project to the ipsilateral VLGN also project to the ipsilateral superior colliculus.…”
Section: Discussionmentioning
confidence: 97%
“…NADPH-d-positive/GABA-IR neurons in the rat DLGN represent a subpopulation of inhibitory interneurons with the ability to affect intrinsic DLGN operations and thalamocortical interactions using neuromodulator NO. Born and Schmidt (2008) reported that inhibitory postsynaptic currents evoked from the pretectal nuclear complex in VLGN neurons are mediated only by GABAA receptors, whereas those evoked in pretectal nuclear complex neurons by VLGN stimulation are mediated either by both GABAA and GABAC receptors or by a GABA receptor with mixed GABAA and GABAC receptor-like pharmacology. Also, they used retrograde double-labeling experiments with two different fluorescent dextran amines to show that pretectal neurons that project to the ipsilateral VLGN also project to the ipsilateral superior colliculus.…”
Section: Discussionmentioning
confidence: 97%
“…These multisensory inputs include direct visual projections from retina and the lateral geniculate nucleus of the thalamus (Figures 5E,F; Nagata and Hayashi, 1984; Born and Schmidt, 2008), somatosensory, and nociceptive inputs from the trigeminal nuclei (Figures 5M,N,M′,O′), parabrachial nucleus (Figures 5K,K′; Killackey and Erzurumlu, 1981; Ricardo, 1981; Huerta et al, 1983; May, 2006), and cuneiform nucleus (Carlson et al, 2004), auditory input from nucleus of the lateral lemniscus and nucleus sagulum (Figures 5J,J′; Henkel and Schneiderman, 1988; Kelly et al, 1998, 2009; Bajo et al, 1999). Among these sensory afferents it appears that vibrissae-related signals from the oral trigeminal nucleus are directed preferentially to the rostrolateral enlargement of the SC deep layers where they play a critical role in approach movements such as those associated with predatory hunting (Figure 5O′; Furigo et al, 2010; Favaro et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that GABAρ subunits are expressed in the brain cortex, thalamus, hippocampus, superior colliculus, cerebellum, and spinal cord [99-104], ventral and dorsal lateral geniculate nuclei [105, 106], thyrotropin secreting cells of the pituitary [99, 107], the dorsolateral geniculate gyrus of the thalamus [108], and pretectal nucleus of the optic tract [109]. However, there are other areas of the CNS where their expression of GABAρ subunits remains to be determined or is puzzling.…”
Section: Distribution In the Cns And Beyondmentioning
confidence: 99%